Physical activity assessments in obese and non-obese adolescents using the Bouchard diary - Fitri Primacakti; Damayanti R. Sjarif; Najib Advani (Paediatrica Indonesiana, 2014)
Background Obesity is now a global epidemic problem. Increasedprevalence of obesity is associated with increased sedentarybeh avior and low physical activity.Objective To assess the physical activity patterns of adolescentsaged 10-15 years and to compare mean energy output, intensityof physical activity, duration of moderate-vigorously intensity ofphysical activity, and length of screen time in obese and non-obeseadolescents.Methods This cross-sectional study was conducted on 7th and3th grade students aged 12-15 years at 216 junior high schools inWest Jakarta. Physical activity was assessed using th e Boucharddiary for 2 school days and 1 holiday.Results There was no significant differen ce in mean energyoutput between th e obese and non-obese adolescent s. Th emedian intensity of physical activity of obese adolescents waslower than that of non-obese adolescents [1.5 (range 0.8 to 1.8)vs. 2 (range 1.6 to 2.8) METs, respectively; P <0.00 1] . The meanduration of moderate-vigorous intensity of physical activity inobese adolescents was shorter than that of non-obese adolescents[19.3 (SD 6.9) vs. 26.4 (SD3.4) minutes, respectively; P= 0.000].Median length of screen time was longer for obese adolescentsthan for non -obese adolescents [2.8 (range 1 to 6.6) vs. 1.8(range 0.3 to 6.1) hours, respectively; P < 0.001]. There was noadolescent who met the recommended physical activity intensityand duration criteria.Conclusion Physical activity varies among adolescents aged10- 15 years. Obese adolescents have signific antly less physicalactivity duration and intensity than n on-obese adolescents, butsignificantly longer screen time. All adolescents' physical activityis less than the recommended intensity and duration.